ANALYSIS OF THE ROLE OF INTRACAMPUS STUDENT ORGANIZATIONS IN CHARACTER BUILDING: STUDENT URGENCE IN THE DIGITAL GENERATION (Lembaga Pengembangan Kinerja Dosen, 2022)
This study aims to determine the role of student organizations in building character, especially in today's digital generation. In conducting this research, the author applies a qualitative or descriptive literature study research method. Literature studies are obtained through a literacy process from various books and articles related to the material to be discussed. The literature study in this study was carried out by the author through the process of reading, concluding, then processing and developing the data obtained as material from the research conducted. Based on the research carried out, it was concluded that the very important role of student organizations in educating student character in this digital era is critical thinking. If students do not have the ability to think critically, it will be very easy to fall into things that weaken the character of the nation. Students must be able to be good examples for the community and the task of students is also to make the best possible use of existing digital technology and then implement it in everyday life. This research is expected to provide information and add insight to readers, especially students, about the role of student organizations in the digital generation.